Stingless Bees (Melipona subnitida) Overcome Severe Drought Events in the Brazilian Tropical Dry Forest by Opting for High-Profit Food Sources - Maia-Silva, Camila; Limão, A. A.C.; Silva, C. I.; Imperatriz-Fonseca, V. L.; Hrncir, M. (Springer Nature, 2020)
In the Brazilian Tropical Dry Forest, the Caatinga, stingless bees (Apidae, Meliponini) need to adjust their foraging behavior to a very short and unpredictable blooming period. Melipona subnitida Ducke 1910 is one of the few meliponine species adapted to the environmental peculiarities of this biome. To get an insight into how these highly eusocial bees are able to maintain their perennial colonies despite extended periods of food scarcity, we asked the following questions: (1) At which plant species do colonies of M. subnitida collect their food during the rainy season? And (2) are there any plant species during the dry season, from which the colonies may profit for replenishing their food stores? During 1 year, we collected monthly honey and pollen samples from recently built storage pots of five colonies of M. subnitida and identified the botanical origin of the collected resources. In the course of our study, the colonies foraged at native trees, shrubs, and herbaceous species, demonstrating the importance of all plant strata for the bees’ diet. Profitable plants, which bloom mainly during the rainy season and usually produce a great number of flowers, were frequently sampled in new pots throughout the entire study, even during the dry season. From our results, we compiled a list of the most important plant species providing floral resources for bees throughout the year, including periods of drought. We recommend these plants for restoration areas to improve the conservation of native bee species and local beekeeping in the Brazilian Tropical Dry Forest.
Keywords: Caatinga; jandaíra; Meliponini; melittopalynology; pot-honey; pot-pollen